Composite powder for secondary battery binder
By coating the secondary battery binder particles to form a composite powder, the problem of slow dissolution of the binder in the solvent is solved, and a more efficient electrode processing process is achieved.
Patent Information
- Application Number
- CN202311373389.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
The dissolution rate of existing secondary battery binders in the solvent is slow, which affects the efficiency of the electrode processing technology.
By coating the binder particles with a powder with a particle size smaller than the binder particles, a composite powder is formed, and agglomeration between the binder particles is inhibited, and its dispersion and dissolution rate in the solvent are improved.
While maintaining the bonding performance, the dissolution rate of the adhesive in the solvent is significantly improved, the electrode processing technology is optimized, and the process flow and processing time is shortened.
Smart Images

Figure BDA0004508637020000131 
Figure HDA0004508637180000011 
Figure HDA0004508637180000012
Abstract
Description
Technical Field
[0001] The invention relates to a composite powder for a secondary battery binder. Background Art
[0002] In addition to good bonding properties, the binder materials used in the electrodes of secondary batteries also need to be able to withstand the swelling and corrosion of the electrolyte, as well as the electrochemical corrosion during the charge and discharge process, and remain stable within the working voltage range of the electrode. Therefore, there are not many polymer materials that can be used as electrode binders. Currently, the widely used binders for secondary batteries mainly include: polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide (PI) and other oily binders; and carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA), polyacrylamide (PMA) and other water-based binders.
[0003] Electrode binders usually have to be dissolved in a solvent and used in the form of a binder solution so that the binder can fully contact the active material particles and the conductive additive to form a good electronic and ion conductive network. As an ideal binder, it needs to have good solubility in the solvent, fast dissolution rate, and high solubility. However, when commonly used binders such as PVDF are dissolved in a solvent, there is a problem of slow dissolution rate. The main reason is that during the dissolution process of the binder powder, the binder particles are prone to agglomeration to form agglomerates, and the solvent cannot fully penetrate into the center of the agglomerate, resulting in a slower dissolution rate. At the same time, since most of the binders are polymer materials with a large molecular weight, when they are partially dissolved in the solvent, the viscosity of the solution will gradually increase, the stirring speed will be reduced, and the dissolution rate will be slowed down.
[0004] The solubility characteristics of the binder will affect the processing technology of the electrode. If the dissolution rate of the binder in the solvent can be increased, the process flow can be shortened, the processing time can be shortened, and the processing efficiency can be improved. Therefore, it is necessary to seek a technology that can improve the solubility of the binder in the solvent so that the processing technology can be optimized. Summary of the invention
[0005] In view of the above problems in the prior art, the present invention aims to provide a composite powder for a secondary battery binder that can increase the dissolution rate of the binder in a solvent.
[0006] In order to achieve the above-mentioned purpose, the inventors conducted in-depth research and found that by coating the binder particles for secondary batteries with a powder having a particle size smaller than that of the binder particles, the solubility performance of the binder can be improved and the dissolution rate can be increased without affecting the binding performance, chemical stability and electrochemical stability of the binder, thereby completing the present invention.
[0007] That is, the present invention provides a composite powder for a secondary battery binder, which comprises a first powder and a second powder coated on the surface of the first powder, the first powder is a binder particle, and the ratio of the D50 particle size of the second powder to the D50 particle size of the first powder is greater than 1 / 1000 and less than 1 / 1 in terms of particle size of the second powder / particle size of the first powder.
[0008] The binder particles are formed into the form of the composite powder of the present invention, which effectively inhibits the formation of agglomerates due to agglomeration between the binder particles, improves the dispersibility of the binder particles in the solvent, and allows the solvent to easily penetrate into the central part of the binder particles, thereby accelerating the dissolution rate of the binder particles in the solvent.
[0009] In the composite powder of the present invention, the first powder is soluble in a solvent, and the second powder is soluble or insoluble in the solvent. When the second powder is soluble in the solvent, during the dissolution of the first powder, the second powder first dissolves and adsorbs on the surface of the first powder, so that steric hindrance is generated between the first powders, thereby preventing the first powders from contacting each other and agglomerating. On the other hand, when the second powder is insoluble in the solvent, during the dissolution process, the second powder can physically avoid the first powders from contacting each other and agglomerating, thereby effectively inhibiting the occurrence of agglomeration between the binder particles.
[0010] In addition, the solvent is water or an organic solvent, and the organic solvent is at least one selected from N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, acetone, methyl ethyl ketone, dichloroethane, chloroform, acetonitrile, and tetrahydrofuran. By using the above solvent, the binder particles are more fully and quickly dissolved, and have a suitable viscosity, which is beneficial to subsequent processing, reduces the generation of bubbles, and improves battery performance.
[0011] In the composite powder of the present invention, the first powder is selected from a homopolymer or copolymer containing more than 20 mol% of vinylidene fluoride, poly(meth)acrylic acid, styrene-butadiene rubber, poly(meth)acrylamide, polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, xanthan gum, and gum arabic, preferably a homopolymer or copolymer containing more than 20 mol% of vinylidene fluoride. Thus, while fully showing the good adhesion and good electrochemical stability of the secondary battery binder itself, it can also improve its solubility in the solvent and improve processing efficiency.
[0012] In the composite powder of the present invention, the second powder is one or more selected from organic powders and inorganic powders, preferably one or more selected from conductive additives, dispersants and silica gel particles. Thus, the dispersion performance of the first powder in the solvent can be improved, and the dissolution rate of the first powder in the solvent can be further improved. Furthermore, the second powder is more preferably one or more selected from conductive additives. Thus, after the binder is dissolved, there is no need to remove impurities in the binder solution, which greatly simplifies the production process of the electrode, and can also reduce the amount of conductive additives added in subsequent processes, and can ensure the performance of the electrode made using the composite powder.
[0013] In addition, the conductive additive is carbon black, acetylene black, superconducting carbon, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers. By using the above conductive additive as the second powder, good conductive performance can be achieved, and the particle size of the second powder can be easily and uniformly controlled, so that the second powder is uniformly coated on the surface of the first powder.
[0014] In addition, the dispersant is phosphite, polyvinyl pyrrolidone, polyethylene glycol, polyethylene glycol monooctylphenyl ether or ammonium polyacrylate. By using the above dispersant as the second powder, a spatial repulsive force can be generated between the binder particles, further improving the dispersion state of the composite powder, so that the pole piece materials including the binder are evenly dispersed in the slurry, improving the battery performance, and optimizing the viscosity of the slurry, making the slurry easier to handle and increasing the processing speed.
[0015] In the composite powder of the present invention, the D50 particle size of the second powder is 10 nm or more and 50 μm or less. Thus, the second powder can be more evenly coated on the surface of the first powder without affecting the dissolution rate of the first powder in the solvent.
[0016] In the composite powder of the present invention, the mass of the first powder is not less than 50wt% and not more than 99.9wt% of the total mass of the composite powder, thereby ensuring the bonding performance of the composite powder and improving the stability of the battery.
[0017] In the composite powder of the present invention, the coverage rate of the second powder on the surface of the first powder is 50% to 100%, thereby reducing the aggregation of the binder particles and increasing the dissolution rate of the binder particles.
[0018] According to the present invention, a composite powder for a secondary battery binder can be provided which can maintain good bonding performance while having good solubility in a solvent, a faster dissolution rate, and is beneficial to the operability of a battery processing technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1This is a SEM electron microscope photograph of the VDF-TFE binder coated with the second powder obtained in Example 1 (6.0 mm×1.00 k, 5.0 kV).
[0020] Figure 2 This is a partially enlarged SEM electron microscope photograph of the VDF-TFE binder coated with the second powder obtained in Example 1 (6.0 mm×10.00 k, 5.0 kV).
[0021] Figure 3 This is a SEM electron microscope photograph of the PVDF binder coated with the second powder obtained in Example 8 (magnification: 333).
[0022] Figure 4 This is a SEM electron microscope photograph of the uncoated VDF-TFE binder obtained in Comparative Example 4 (magnification: 333). DETAILED DESCRIPTION
[0023] The embodiments of the present invention are described in detail below with reference to the accompanying drawings as appropriate. However, those skilled in the art should understand that the following embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention.
[0024] For simplicity, the present invention specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0025] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0026] In the description herein, it should be noted that, unless otherwise specified, "(meth)acrylic acid" means including both acrylic acid and methacrylic acid. "(meth)acrylamide" means including both acrylamide and methacrylamide.
[0027] For a long time, the pole pieces of secondary batteries have often used materials with bonding properties, which can withstand the swelling and corrosion of the electrolyte, as well as the electrochemical corrosion during the charge and discharge process, and remain stable within the working voltage range of the electrode as binders during the production process. These materials are generally in the form of high molecular polymers. In order to fully bond the positive and negative active materials, the binder is generally used in the form of a solution. In order to ensure the uniformity and stability of the binder solution, the binder needs to be dissolved in a solvent before use. However, due to the van der Waals force between the polymer chains, the binder is easy to agglomerate to form agglomerates, making it difficult for the solvent to penetrate into the agglomerates, resulting in a decrease in the dissolution rate of the binder. At the same time, after part of the binder is dissolved in the solvent, the viscosity of the solution increases, the stirring speed decreases, and the dissolution rate of the binder will gradually decrease. The speed of forming a solution directly affects the production efficiency of the electrode. Therefore, it is urgent to increase the dissolution rate of the binder in the solvent and optimize the production process.
[0028] In view of the technical problems existing in the above-mentioned prior art, the present invention aims to provide a composite powder for secondary battery binder capable of improving the dissolution rate of the binder in a solvent, comprising a first powder and a second powder coated on the surface of the first powder, the first powder being binder particles, and the ratio of the D50 particle size of the second powder to the D50 particle size of the first powder being greater than 1 / 1000 and less than 1 / 1 in terms of particle size of the second powder / particle size of the first powder.
[0029] The inventors have found that when the second powder is coated on the surface of the binder particles to form a composite powder, the agglomeration caused by the van der Waals force between the binder particles can be effectively reduced, thereby avoiding the formation of larger agglomerates. Smaller binder particles have better dispersibility in the solvent, increase the contact area of the solvent with the binder particles, and make it easy for the solvent to penetrate into the center of the binder particles, thereby accelerating the dissolution rate of the binder particles in the solvent and optimizing the electrode processing technology.
[0030] When the ratio of the D50 particle size of the second powder to the D50 particle size of the first powder is too small, the second powder will be too tightly coated on the first powder, and the solvent cannot penetrate the second powder coated on the surface of the first powder well, affecting the dissolution rate of the binder particles. When the ratio of the D50 particle size of the second powder to the D50 particle size of the first powder is too large, the second powder cannot be evenly coated on the surface of the first powder, and the second powder is also easy to precipitate in the obtained binder solution, affecting the operability of the subsequent process. Therefore, the ratio of the D50 particle size of the second powder to the D50 particle size of the first powder is 1 / 1000 or more and less than 1 / 1, preferably 1 / 1000 or more and 1 / 1.5 or less, and more preferably 1 / 1000 or more and 1 / 300 or less.
[0031] In the composite powder of the present invention, the first powder is soluble in a solvent, and the second powder is soluble or insoluble in the solvent. It is known that the first powder as a binder particle must be in the form of a solution to play the role of a binder, so the first powder needs to be soluble in a solvent. When the second powder is soluble in a solvent, the second powder first dissolves and adsorbs on the surface of the first powder during the dissolution of the first powder, so that steric hindrance is generated between the first powders. Through steric hindrance, the binder particles of the first powder can be prevented from agglomerating due to the influence of van der Waals forces. On the other hand, when the second powder is insoluble in the solvent, the second powder physically becomes an obstacle to the agglomeration of the first powder, thereby effectively suppressing the occurrence of agglomeration between the binder particles. Therefore, the second powder can be soluble or insoluble in the solvent.
[0032] Here, "the first powder / second powder is soluble in the solvent" means that, under an environment of 1 atmosphere and 23°C, 1 g of the first powder / second powder is weighed and immersed in 10 g of the solvent, and after 24 hours, 0.5 g or more of the immersed first powder / second powder is dissolved in the solvent. On the other hand, "the second powder is insoluble in the solvent" means that, under an environment of 1 atmosphere and 23°C, 1 g of the second powder is weighed and immersed in 10 g of the solvent, and after 24 hours, the amount of the immersed second powder dissolved in the solvent is less than 0.1 g.
[0033] In addition, the above-mentioned solvent can be a solvent commonly used in secondary batteries for dissolving the binder. As such a solvent, for example, water or an organic solvent can be cited. As an organic solvent, any organic solvent that can dissolve the binder used can be used, specifically, N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, acetone, methyl ethyl ketone, dibromomethane, dichloroethane, chloroform, acetonitrile, tetrahydrofuran, tetramethylurea, etc. can be cited. These can be used alone or in combination of two or more.
[0034] Among them, from the viewpoint of being conducive to more complete and rapid dissolution of the binder particles, making the obtained solution have a suitable viscosity, being conducive to subsequent processing, reducing the generation of bubbles, and improving battery performance, the organic solvent is preferably selected from at least one of N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, acetone, methyl ethyl ketone, dichloroethane, chloroform, acetonitrile, and tetrahydrofuran, and more preferably N-methylpyrrolidone.
[0035] In the composite powder of the present invention, the first powder is a binder commonly used in secondary batteries. Specifically, oily binders such as polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide (PI), and water-based binders such as carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), and polyacrylamide (PMA) can be cited.
[0036] Among them, from the perspective of fully showing the good adhesion and good electrochemical stability of the secondary battery binder itself, improving its solubility in the solvent and improving the processing efficiency, it is preferably selected from a homopolymer or copolymer containing more than 20mol% of vinylidene fluoride, poly (meth) acrylic acid, styrene-butadiene rubber, poly (meth) acrylamide, polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, xanthan gum, and gum arabic. Further, from the perspective of the good adhesion and good electrochemical stability of the secondary battery binder itself, the solubility of the first powder in the solvent can be further improved, and the processing efficiency is more excellent, it is more preferably a homopolymer or copolymer containing more than 20mol% of vinylidene fluoride.
[0037] As a homopolymer or copolymer of vinylidene fluoride, as long as it can be used as a binder for secondary batteries, it is not particularly limited. Specifically, polyvinylidene fluoride, a copolymer of vinylidene fluoride and tetrafluoroethylene, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and 2-carboxyethyl acrylate, a copolymer of vinylidene fluoride and acryloxyethyl succinic acid, a copolymer of vinylidene fluoride and (meth) acrylic acid, etc. can be listed. In addition, in the copolymer of vinylidene fluoride, the minimum proportion of vinylidene fluoride as a structural unit in all structural units is preferably 20mol% or more, more preferably 40mol% or more, more preferably 50mol% or more, more preferably 70mol% or more, and as its upper limit, it can be less than 100mol%.
[0038] In addition, the D50 particle size of the first powder is not particularly limited and can be appropriately set according to the desired performance of the secondary battery. For example, it can be 10nm to 5000μm. Here, the D50 particle size refers to the particle size when the cumulative particle size distribution reaches 50%. The D50 particle size of the first powder can be measured using a laser particle size distribution analyzer.
[0039] In the composite powder of the present invention, it is known that the role of the second powder is to coat the first powder, reduce the interaction between the first powders, and improve the dispersion performance of the first powder in the solvent. Therefore, as long as it can be well dispersed on the surface of the first powder and there is a certain force between the first powder and the first powder to achieve good coating of the first powder, it can be used as the second powder. Specifically, the second powder can use organic powder or inorganic powder. The above powders can be used alone or in combination of two or more.
[0040] Among them, from the viewpoint of being able to achieve a good coating effect on the surface of the first powder, improving the dispersion performance of the first powder in the solvent, and further improving the dissolution rate of the first powder in the solvent, the second powder is preferably selected from one or more of a conductive aid, a dispersant, and silica gel particles. Furthermore, it is known that in the subsequent process of electrode production, it is necessary to artificially add a conductive aid to increase the conductivity of the electrode. Therefore, when a conductive aid is used as the second powder, the amount of conductive aid added in the subsequent process can be reduced. After the binder is dissolved, there is no need to remove impurities in the binder solution, which greatly simplifies the production process of the electrode. Furthermore, the conductive aid can be more evenly dispersed in the solvent, which is conducive to the uniform distribution of the conductive aid on the entire electrode sheet and improves the conductivity of the electrode. Therefore, the second powder is more preferably selected from one or more conductive aids.
[0041] In addition, the conductive auxiliary agent can be any conductive auxiliary agent commonly used in secondary batteries. Specifically, carbon black, acetylene black, superconducting carbon, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, etc. are preferably used. The conductive auxiliary agent has excellent conductive properties, a stable structure, a controllable and uniform powder size, and can be uniformly coated on the surface of the first powder, so it is preferred.
[0042] In addition, the dispersant is not particularly limited as long as it is a dispersant commonly used in the manufacture of the pole piece of the secondary battery. Specifically, phosphite, polyvinyl pyrrolidone, polyethylene glycol, polyethylene glycol monooctylphenyl ether, ammonium polyacrylate, etc. can be listed. By using the above dispersant as the second powder, a spatial repulsive force can be generated between the binder particles, further improving the dispersion state of the composite powder, so that the pole piece materials including the binder are evenly dispersed in the slurry, improving the battery performance, and at the same time optimizing the viscosity of the slurry, making the slurry easier to handle and increasing the processing speed.
[0043] Furthermore, the D50 particle size of the second powder is greater than 10nm and less than 50μm. When the D50 particle size of the second powder is too small, the second powder will be too tightly coated on the first powder, and the solvent cannot penetrate the second powder coated on the surface of the first powder well, affecting the dissolution rate of the binder particles. When the D50 particle size of the second powder is too large, the second powder cannot be evenly coated on the surface of the first powder, and the second powder is also easy to precipitate in the obtained binder solution, affecting the operability of the subsequent process. In addition, the D50 particle size of the second powder is preferably greater than 100nm and less than 50μm, and more preferably greater than 150nm and less than 50μm. The D50 particle size of the second powder can also be measured using a laser particle size distribution analyzer, similar to the first powder.
[0044] In the composite powder of the present invention, the mass of the first powder is more than 50wt% and less than 99.9wt% of the total mass of the composite powder. When the mass of the first powder accounts for too low a proportion of the total mass of the composite powder, the content of the effective binder decreases, resulting in the need to add a larger amount of composite powder to ensure sufficient bonding performance, which prolongs the process time and increases the complexity of the operation. When the mass of the first powder accounts for too high a proportion of the total mass of the composite powder, the amount of the second powder is insufficient, and it is impossible to achieve sufficient coating on the surface of the first powder, and it is impossible to effectively avoid the van der Waals force between the first powders. Agglomerates are still easily formed, which reduces the dissolution rate of the first powder. Furthermore, the mass of the first powder is preferably more than 70wt% of the total mass of the composite powder, more preferably more than 80wt%, and preferably less than 99wt% of the total mass of the composite powder.
[0045] In the composite powder of the present invention, the coverage rate of the second powder on the surface of the first powder is greater than 50% and less than 100%. As a result, the agglomeration between the binder particles can be fully suppressed and the dissolution rate of the binder can be increased. When the coverage rate of the second powder on the surface of the first powder is too low, the van der Waals effect between the first powders cannot be effectively avoided, and agglomerates are still easily formed. Furthermore, the coverage rate of the second powder on the surface of the first powder is preferably greater than 60% and less than 100%, more preferably greater than 80% and less than 100%, and more preferably greater than 85% and less than 98%.
[0046] The coverage rate can be obtained by a method known in the art. For example, the coverage rate can be calculated by taking a 200- to 1000-fold magnified photograph of the composite powder using a video microscope, binarizing the obtained photograph using image analysis software, and then calculating the coverage rate using the following formula.
[0047] Coverage (%) = S2 / (S1+S2)×100
[0048] (Wherein, S1 represents the area of the first powder not covered by the second powder, and S2 represents the area of the first powder covered by the second powder.)
[0049] The image analysis software used for the binarization process is not particularly limited, and for example, Image J, which is free software published by the National Institutes of Health (NIH) of the United States, can be used.
[0050] In addition, the coverage can also be determined using a scanning electron microscope (SEM) and element mapping method. Depending on the mixing state of the first powder and the second powder or the color of the filler material, it is sometimes difficult to calculate the coverage through an optical microscope photograph. For example, when the first powder and the second powder are similar in color and shape and only differ in size, it is difficult to distinguish their boundaries using an optical microscope photograph. In this case, a method of determining the coverage by SEM and element mapping is effective. Based on the above-mentioned SEM and element mapping coverage, after element mapping of fluorine is performed using SEM (SU5000 Scanning Electron Microscope manufactured by HITACHI) and imaging, the image is binarized and the coverage can be obtained by the same method as that for calculating the coverage from a video microscope image.
[0051] In addition, the composite powder of the present invention may also include a third powder within the scope of not impairing the effect of the present invention. The third powder may be coated on the surface of the first powder in the same manner as the second powder, or may be coated on the surface of the second powder. As the third powder, commonly used additives commonly used for pole pieces of secondary batteries can be used. Specifically, lithium supplements such as lithium-rich transition metal oxides, anionic polymer additives, etc. can be listed.
[0052] By utilizing the composite powder of the present invention, while maintaining good bonding performance, it has better solubility in the solvent and faster dissolution rate, which is beneficial to the optimization of the battery processing technology.
[0053] The composite powder of the present invention can be manufactured by coating the second powder on the surface of the first powder using a commonly used method. Specifically, a dry method, a wet method, and the like can be cited. As a dry method, a method in which the first powder and the second powder are mixed by stirring, and the second powder is coated on the surface of the first powder can be cited. As stirring, manual stirring or stirring using a mechanical device can be cited, and as a mechanical device, an air flow mixer, a ball mill, and the like can be used. As a wet method, a method in which the second powder is uniformly dispersed in a solvent to obtain a dispersion of the second powder, the dispersion is sprayed on the surface of the first powder, and then it is dried can be cited.
[0054] Example
[0055] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0056] Example 1
[0057] As the first powder, a copolymer of vinylidene fluoride and tetrafluoroethylene (VDF-TFE copolymer, the proportion of vinylidene fluoride in the copolymer is 70 to 85 mol%) (manufactured by Daikin, VT475) with a D50 of 125 μm was used, and as the second powder, carbon black (manufactured by IMERYS, Super-P) with a D50 of 0.2 μm was used. 5 g of the first powder and 5 g of the second powder were taken respectively, and mixed by manual stirring to form a composite powder A. The electron microscope photograph of the composite powder A and the partially enlarged electron microscope photograph of the particle surface are shown in Figure 1 and Figure 2 In. From Figures 1-2 It can be confirmed that the surfaces of the binder particles are coated with carbon black powder.
[0058] Example 2
[0059] Composite powder B was formed in the same manner as in Example 1 except that 4.95 g of the first powder and 0.05 g of the second powder were taken.
[0060] Example 3
[0061] Composite powder C was formed in the same manner as in Example 1 except that 4.995 g of the first powder and 0.005 g of the second powder were taken.
[0062] Example 4
[0063] As the first powder, polyvinylidene fluoride (PVDF) (manufactured by Fonolin, FL2000) with a D50 of 68 μm was used, and as the second powder, carbon black (manufactured by IMERYS, Super-P) with a D50 of 0.2 μm was used. 5 g of the first powder and 5 g of the second powder were taken respectively. Except for this, composite powder D was formed in the same manner as Example 1.
[0064] Example 5
[0065] Composite powder E was formed in the same manner as in Example 4 except that 5 g of the first powder and 2.14 g of the second powder were taken.
[0066] Example 6
[0067] Composite powder F was formed in the same manner as in Example 4 except that 4.95 g of the first powder and 0.05 g of the second powder were taken.
[0068] Example 7
[0069] Composite powder G was formed in the same manner as in Example 4 except that 4.995 g of the first powder and 0.005 g of the second powder were taken.
[0070] Example 8
[0071] As the first powder, polyvinylidene fluoride (PVDF) (manufactured by Fonolin, FL2000) with a D50 of 68 μm was used, and as the second powder, polyvinyl pyrrolidone (PVP) (manufactured by Guangdong Yuemei Chemical Co., Ltd., PVP-K30) was classified by sieving so that its D50 became 40 μm. 4.95 g of the first powder and 0.05 g of the second powder were taken respectively, and the composite powder H was formed in the same manner as in Example 1 except that the above-mentioned steps were repeated.
[0072] Example 9
[0073] As the first powder, a VDF-TFE copolymer (manufactured by Daikin, VT475) having a D50 of 125 μm was used, and as the second powder, a powder obtained by sieving polyvinyl pyrrolidone (PVP) (manufactured by Guangdong Yuemei Chemical Co., Ltd., PVP-K30) was classified so that its D50 was 40 μm. 4.95 g of the first powder and 0.05 g of the second powder were taken respectively, and composite powder I was formed in the same manner as in Example 1 except that the above-mentioned steps were repeated.
[0074] Comparative Example 1
[0075] As the first powder, 5 g of a VDF-TFE copolymer (Daikin, VT475) having a D50 of 125 μm was used, and the first powder was used as it was as powder A′ without coating the first powder with the second powder.
[0076] Comparative Example 2
[0077] As the first powder, 5 g of PVDF (manufactured by Fonolin, FL2000) having a D50 of 68 μm was used, and the first powder was used as it was as powder B′ without coating the first powder with the second powder.
[0078] Comparative Example 3
[0079] As the first powder, 4.95 g of PVDF (manufactured by Fonolin, FL2000) with a D50 of 68 μm was used, and as the second powder, 0.05 g of carbon black (manufactured by IMERYS, Super-P) with a D50 of 0.2 μm was used. Without mixing the first powder and the second powder, the first powder and the second powder were put into a container in sequence, and NMP was added as powder C' so that the solid content of the binder component became 5 wt%, and then the following test was started.
[0080] Comparative Example 4
[0081] As the first powder, 4.95 g of VDF-TFE copolymer (Daikin, VT475) with a D50 of 125 μm was used, and as the second powder, 0.05 g of polyvinyl pyrrolidone (PVP) (manufactured by Guangdong Yuemei Chemical Co., Ltd., PVP-K30) was graded by sieving so that its D50 became 40 μm. Without mixing the first powder and the second powder, the first powder and the second powder were put into a container in sequence, and NMP was added as powder D' so that the solid content of the binder component became 5wt%, and then the following test was started.
[0082] The composite powders A to I obtained in Examples 1 to 9 and the powders A' to D' obtained in Comparative Examples 1 to 4 were subjected to the following tests by the following methods. The obtained results are shown in Table 1 below.
[0083] 1. Coverage test
[0084] The coverage ratio was calculated by binarizing a 200- to 1000-fold magnified photograph of the composite powder taken using a video microscope (VHX-7100 manufactured by KEYENCE) using image analysis software Image J, and then using the following formula.
[0085] Coverage (%) = S2 / (S1+S2)×100
[0086] (Wherein, S1 represents the area of the first powder not covered by the second powder, and S2 represents the area of the first powder covered by the second powder.)
[0087] In addition, when the first powder and the second powder are similar in color and shape and only differ in size, it is difficult to distinguish their boundaries using an optical microscope photograph. In this case, the coverage is obtained by performing elemental mapping of fluorine using a SEM (SU5000 Scanning Electron Microscope manufactured by HITACHI) and imaging the image, then binarizing the image and using the same method as that for calculating the coverage from a video microscope image.
[0088] 2. Solubility test
[0089] Take 5g of the composite powders A to I obtained in Examples 1 to 9 and the powders A' to D' obtained in Comparative Examples 1 to 4, respectively, and add an appropriate amount of N-methylpyrrolidone as a solvent to make the solid content of the effective binder component reach 5wt%. Then, stir with a stirring device with a stirring paddle to dissolve the powder, and start timing until no solid particles remain by naked eye observation, and record the time required for dissolution. Then, use a filter (mesh size 250 mesh) to filter the fully dissolved solution to ensure that no solid particles remain in the solution. Then, use a fineness meter (manufactured by Shanghai Modern Environmental Engineering Technology Co., Ltd.) to confirm whether there are agglomerated particles in the solution. If no particles are found to remain after filtration, the obtained time is used as the time required for the binder particles to fully dissolve; if particles are found to remain after filtration, repeat the above test until no binder particles are found to remain.
[0090] [Table 1]
[0091]
[0092] From the results in Table 1, it can be seen that in Examples 1 to 9, after the surface of the binder particles is coated with the second powder, the agglomeration of the binder particles is suppressed, the binder particles are easily dispersed in the solvent, and the dissolution rate is significantly accelerated. In contrast, in Comparative Examples 1 and 2, the binder particles agglomerate, and the dissolution rate of the binder particles in the solvent is slow, which affects the electrode process flow. In Comparative Examples 3 to 4, the second powder does not fully coat the surface of the binder particles, resulting in the binder particles still being easy to contact each other and agglomerate, causing the binder particles to dissolve slowly in the solvent.
[0093] Those skilled in the art should understand that the above embodiments are only some specific embodiments for implementing the present invention, and in practical applications, various changes and modifications may be made thereto in form and details, all of which fall within the protection scope of the present invention.
Claims
1. A composite powder for a secondary battery binder, characterized in that: The invention comprises a first powder and a second powder coated on the surface of the first powder, wherein the first powder is a binder particle. The ratio of the D50 particle size of the second powder to the D50 particle size of the first powder is 1 / 1000 or more and less than 1 / 1 in terms of particle size of the second powder / particle size of the first powder.
2. The composite powder for secondary battery binder according to claim 1, characterized in that: The first powder is soluble in a solvent, and the second powder is soluble or insoluble in the solvent.
3. The composite powder for secondary battery binder according to claim 2, characterized in that: The solvent is water or an organic solvent, The organic solvent is at least one selected from N-methylpyrrolidone, dimethyl sulfoxide, dimethylacetamide, dimethylformamide, trimethyl phosphate, triethyl phosphate, acetone, methyl ethyl ketone, dichloroethane, chloroform, acetonitrile and tetrahydrofuran.
4. The composite powder for secondary battery binder according to claim 2 or 3, characterized in that: The solvent is N-methylpyrrolidone.
5. The composite powder for secondary battery binder according to any one of claims 1 to 4, characterized in that The first powder is selected from a homopolymer or copolymer containing more than 20 mol% of vinylidene fluoride, poly(meth)acrylic acid, styrene-butadiene rubber, poly(meth)acrylamide, polyvinyl alcohol, sodium alginate, carboxymethyl cellulose, xanthan gum, and gum arabic, preferably a homopolymer or copolymer containing more than 20 mol% of vinylidene fluoride.
6. The composite powder for secondary battery binder according to any one of claims 1 to 5, characterized in that The second powder is one or more selected from organic powders and inorganic powders, preferably one or more selected from conductive additives, dispersants and silica gel particles, and more preferably one or more selected from conductive additives.
7. The composite powder for secondary battery binder according to claim 6, characterized in that: The conductive additive is carbon black, acetylene black, superconducting carbon, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.
8. The composite powder for secondary battery binder according to claim 6, characterized in that: The dispersant is phosphite, polyvinyl pyrrolidone, polyethylene glycol, polyethylene glycol monooctylphenyl ether or ammonium polyacrylate.
9. The composite powder for secondary battery binder according to any one of claims 1 to 8, characterized in that The D50 particle size of the second powder is greater than or equal to 10 nm and less than or equal to 50 μm.
10. The composite powder for secondary battery binder according to any one of claims 1 to 9, characterized in that The mass of the first powder is greater than or equal to 50 wt % and less than or equal to 99.9 wt % of the total mass of the composite powder.
11. The composite powder for a secondary battery binder according to any one of claims 1 to 10, characterized in that The coverage rate of the second powder on the surface of the first powder is greater than or equal to 50% and less than or equal to 100%.